BTK Inhibition Impairs the Innate Response Against Fungal Infection in Patients With Chronic Lymphocytic Leukemia - Fiorcari, Stefania; Maffei, Rossana; Vallerini, Daniela; Scarfò, Lydia; Barozzi, Patrizia; Maccaferri, Monica; Potenza, Leonardo; Ghia, Paolo; Luppi, Mario; Marasca, Roberto (Frontiers in Immunology, 2020)
Infections represent a cause of morbidity and mortality in patients affected by chronic lymphocytic leukemia (CLL). Introduction of new drugs in CLL clinical practice has showed impressive efficacy, in particular those targeting BTK. Among the consistent clinical data, an increasing number of reports describing the occurrence of unexpected opportunistic fungal infections has been reported during treatment with ibrutinib in the first 6 months of treatment. The reason underlying manifestations of invasive fungal infections in patients treated with ibrutinib is still under investigation. Our study aimed to understand the impact of BTK inhibition on immune response to fungal infection mediated by macrophages and CD14+ monocytic population obtained from CLL patients. Exposure to ibrutinib and acalabrutinib reduced signaling pathways activated by A.fumigatus determining an exacerbation of an immunosuppressive signature, a reduction of phagocytosis and a significant deficit in the secretion of inflammatory cytokines either in macrophages and monocytes isolated from CLL patients and healthy donors. These effects lead to a failure in completely counteracting conidia germination. In addition we investigated the biological effects of ibrutinib on monocyte counterpart in patients who were undergoing therapy. A significant impairment in cytokine secretion and a deficit of phagocytosis in circulating monocytes were detected after 3 months of treatment. Thus, our results uncover modifications in the innate response in CLL patients induced by ibrutinib that may impair the immunological response to fungal infection.